PERENCANAAN PENGENDALIAN PRODUKSI DAN PERSEDIAAN INDUSTRI PASTA PT âXYZâ - Nurhasanah, Nunung (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
Pasta industry is a very interisting topic to be solved by production planning and inventory control approach. Because of the raw material is wheat cernel that would not found in Indonesia, so it is important to manage the inventory and production. Wheat cernel that use for pasta industry is ones who growth in sub tropics country. Indonesia is a tropic country, that is why to produce pasta, Indonesia has to import from United Stated of America or Australia. Â